Effect of Carbon Fiber Surface Microstructure on Composite Interfacial Property Based on Image Quantitative Characterization Technique - Shu Xiong (MDPI AG, 2021)
The surface roughness (Ra) and composite interfacial property of carbon fiber (CF) are considered to be mainly affected by the microstructure of the CF surface. However, quantitative characterization of the CF surface microstructure is always a difficulty. How the CF surface microstructure affects the interfacial property of CF composites is not entirely clear. A quantitative characterization technique based on images was established to calculate the cross-section perimeter and area of five types of CFs, as well as the number (N), width (W) and depth (D) of grooves on these CF surfaces. The CF composite interfacial shear strength (IFSS) was tested by the micro-droplet debonding test and modified by the realistic perimeter. The relationship between the groove structure parameter and the Ra, specific surface area and composite interfacial property was discussed in this article. The results indicated that the CF cross-section perimeter calculated by this technique showed strong consistency with the CF specific surface area and composite interfacial property. At last, the composite interface bonding mechanism based on defect capture was put forward. This mechanism can be a guiding principle for CF surface modification and help researchers better understand and establish interface bonding theories.